2018
DOI: 10.1136/archdischild-2018-314985
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and aetiology of paediatric traumatic cardiac arrest in England and Wales

Abstract: ObjectiveTo describe the epidemiology and aetiology of paediatric traumatic cardiac arrest (TCA) in England and Wales.DesignPopulation-based analysis of the UK Trauma Audit and Research Network (TARN) database.Patients and settingAll paediatric and adolescent patients with TCA recorded on the TARN database for a 10-year period (2006–2015).MeasuresPatient demographics, Injury Severity Score (ISS), location of TCA (‘prehospital only’, ‘in-hospital only’ or ‘both’), interventions performed and outcome.Results21 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
2
10
1
2
Order By: Relevance
“…In traumatic OHCA paediatric patients, the survival rate at Day 30 varied between 0 and 25.6%, with a pooled rate of 1.2%. We reported only a 2% Day 30 survival rate in our traumatic OHCA population, lower than previously reported in other countries (3.4% in Japan [23], 4.7% in England and Wales [24], and 5.4% in the USA and Canada [3,19]). The prehospital emergency systems are different between countries, which may explain this difference.…”
Section: Discussioncontrasting
confidence: 82%
“…In traumatic OHCA paediatric patients, the survival rate at Day 30 varied between 0 and 25.6%, with a pooled rate of 1.2%. We reported only a 2% Day 30 survival rate in our traumatic OHCA population, lower than previously reported in other countries (3.4% in Japan [23], 4.7% in England and Wales [24], and 5.4% in the USA and Canada [3,19]). The prehospital emergency systems are different between countries, which may explain this difference.…”
Section: Discussioncontrasting
confidence: 82%
“…Fundamentally, we agree with the authors that “hemostasis, volume resuscitation and high-quality CPR” should be prioritised in major haemorrhage; however, we feel that the results of this study should be interpreted with caution and is unlikely to affect our current practice. This study, however, reaffirms the very poor prognosis associated with this catastrophic injury type [5].…”
supporting
confidence: 76%
“…We have demonstrated that paediatric TCA is rare,2 and we respectfully suggest that VF within this cohort is an even rarer presenting rhythm.…”
mentioning
confidence: 54%